EFEKTIVITAS PEMBELAJARAN SECARA TATAP MUKA TERBATAS PADA MASA PANDEMI COVID-19 DI KELAS X MIA SMA NEGERI 1 SUNGAI RAYA - Aufa Zahra; Imam Ghozali; Nurmila Sari Djau (Universitas Tanjungpura, 2022)
This study was motivated by the problem of the teaching-learning process on Art & Culture subject which was conveyed through limited face-to-face teaching-learning to the tenth-grade science students at SMA Negeri 1 Sungai Raya. The purpose of this study was to describe the effectiveness of learning Arts and Culture conducted in a limited way in class X MIA at SMA Negeri 1 Sungai Raya. This study used a qualitative research method with a descriptive design. In this study, the data was obtained using several techniques: observation, interviews, and documentation. The techniques used to test the data's validity were lengthening observations, triangulation techniques, and triangulation of sources. The result of this research showed that the learning of Arts and Culture in the material of singing Indonesia Raya song 3 Stanza, which was done with limited face-to-face teaching – learning, was ineffective. This was happened due to the lack of time in the teaching-learning process led to the materials conveyed considerably lack, and at the time of taking grades, not all students had chance to come forward, and some students were not focus during the teaching-learning activity. The researcher hoped that by conducting this study, the result could help fixing the teaching – learning process which was conveyed through limited face to face teaching – learning become more effective.